2016
DOI: 10.1111/1556-4029.13068
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Investigation of Formaldehyde in Illicit Products for Hair Treatment by DADHPLC: A Case Study

Abstract: The illegal use of formalin (commercial formaldehyde) in cosmetic products harms the health of individuals exposed to this substance. Over the last years, the commercial availability of these products, especially those containing irregular dosage of formaldehyde, has increased in Brazil. This work analyzes some products for hair treatment available in the Brazilian market and verifies their safety. The adopted analytical methodology involved sample derivatization with 2,4-dinitrophenylhydrazine, followed by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
4
1
Order By: Relevance
“…However, very few studies have investigated formaldehyde in hair-straightening products. Oiye et al (2016) analyzed five samples of these products sold in Brazil and found two samples containing levels of 0.02 and 0.03% and three samples at levels from 9.2 to 18.4%, much higher than those found in the present study. In the United Sates, the Environmental Working Group investigated 16 companies that make hair-straightening products that are commercialized in the country (EWG, 2011).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…However, very few studies have investigated formaldehyde in hair-straightening products. Oiye et al (2016) analyzed five samples of these products sold in Brazil and found two samples containing levels of 0.02 and 0.03% and three samples at levels from 9.2 to 18.4%, much higher than those found in the present study. In the United Sates, the Environmental Working Group investigated 16 companies that make hair-straightening products that are commercialized in the country (EWG, 2011).…”
Section: Discussioncontrasting
confidence: 80%
“…Various analytical methods to detect formaldehyde in cosmetic and pharmaceutical products have been reported, including the semi-qualitative chromotropic acid (CA) colorimetric method (Hauksson et al, 2016;Malinauskiene et al, 2015), spectrophotometry after derivatization with acetylacetone (Brandão, Ramos, Rodrigues, 2018), HPLC-UV after derivatization with 2,4-dinitrophenylhydrazine (Golden, Valentini, 2014;Soman, Qiu, Chan, 2008;Oiye et al, 2016), HPLC separation followed by derivatization with 3,5-diacetyl-1,4-dihydrolutidine spectrophotometry (Miralles et al, 2018) and headspace-gas-chromatography (HS-GC) after derivatization with ethanol (Del Barrio et al, 2006;Daoudy et al, 2018). Under acidic conditions, methylal or ethylal can be prepared through the reaction of formaldehyde and methanol or ethanol, and etoxymethoxymethane (EMM) is formed when both alcohols are present (Cao et al, 2009;Chopade, Sharma;1997;Zhang, Zhang, Jian, 2011), as shown in Figure 1.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…As it is crucial to reach an equilibrium before the solutions are transferred into vials for analysis, a 50-minute derivatisation was selected; this is lower than times employed by some methods in the literature [ 12 , 14 , 48 ]. If time is a critical factor, lower derivatisation times (30–35 minutes) may be employed, as shown in Figure 2 , similarly to other derivatisation methods found in the literature [ 53 , 56 , 67 ]. Standard and sample solution stability was successfully demonstrated when using this derivatisation time, as described in the “Standard and sample stability” section.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the hydroxide and thio-based straighteners, formaldehyde and glutaraldehyde, have been actively used for hair straightening, despite having been banned due to their toxicity, simply because they are inexpensive and result in shiny, straight hair through the crosslinking of the amine groups in the keratin [6]. Formaldehyde is even more dangerous compared to glutaraldehyde as it causes serious damage to tissues and the respiratory tract of users, as well as those of the hairdressers working in salons, and has been classified as a carcinogen [6,9,12].…”
Section: Introductionmentioning
confidence: 99%